Entrepreneurial Hadhanah: Islamic Family Law, Habitus Formation, and Intergenerational Entrepreneurship Among Muslim Artisan Families In Indonesia - Maisaroh Harahap; Ya' Rakha Muyassar; Nurhidayati Nurhidayati; Maman Rahman Hakim; Nur Ihsan Hinna (Universitas Muhammadiyah Bandung, 2025)
Studies on hadhanah in Islamic family law have predominantly focused on child custody, parental responsibilities, and post-divorce welfare, leaving limited attention to its role in fostering children's capabilities within entrepreneurial Muslim families. This study addresses this gap by examining how hadhanah functions as a socio-legal process of moral education, entrepreneurial socialization, and intergenerational transmission of values while maintaining child protection principles. Employing a qualitative socio-legal approach with a multi-site case study design, the research was conducted among Muslim artisan families in Tasikmalaya, Pekalongan, and Kudus, Indonesia. Data were collected through in-depth interviews, life-history interviews, participant observation, and document analysis involving Muslim entrepreneurial families, business successors, religious and community leaders, MSME practitioners, and local stakeholders. The data were analyzed thematically by integrating classical Islamic jurisprudence on hadhanah with the framework of maqāṣid al-sharīʿah to assess the compatibility of entrepreneurial exposure with child welfare, education, safety, and protection from exploitation. The findings reveal that hadhanah extends beyond physical care and religious instruction to encompass age-appropriate entrepreneurial learning through the gradual transmission of Islamic values, including honesty (amanah), discipline, diligence, responsibility, and lawful livelihood. Children acquired practical competencies in production, marketing, inventory management, and customer relations alongside soft skills such as communication, negotiation, patience, trust-building, and decision-making. The study proposes the concept of entrepreneurial hadhanah, which reconceptualizes Islamic child care as a framework for capability development rather than merely post-divorce custody, while preserving normative safeguards centered on proportionality, child welfare, education, safety, and children's agency. This conceptual contribution broadens contemporary Islamic family law discourse by integrating child protection with sustainable entrepreneurial capacity development.